Methicillin-Resistant Staphylococcus aureus: Treatment with Cultures of Non Drug-Resistant Staphylococcus epidermidis - Werner, Felix-Martin; Covenas, Rafael (Recent Patents on Anti-Infective Drug Discovery, 2015)
The colonization and infection with methicillin-resistant Staphylococcus aureus is a major health problem in hospitals and long-term care facilities. Although bacteriaemias with MRSA (methicillin-resistant Staphylococcus aureus) can be treated with vancomycin and other reserve antibiotics, 20% of patients cannot be successfully cured. Inpatients colonized with MRSA are isolated in hospitals according to the guidelines of the Robert-Koch-Institute, although in long-term care facilities these patients are not urgently isolated. Active decolonization measures are taken to eradicate colonization with MRSA. In order to reduce MRSA colonization, it could be possible to administer cultures of Staphylococcus epidermidis which have no antibiotic resistance, so that physiological genes could be conferred from Staphylococcus epidermidis to MRSA bacteria.
Keywords: multi-resistance